An optical nano-antenna system design for radio therapeutic use - N. Thammawongsa; S. Mitatha; P. P. Yupapin (My University, 2012)
This paper proposes a nano-antenna system using the optical spins generated by a PANDA ring resonator for radio therapeutic applications. Initially, the magnetic field is induced by the coupling effects between aluminium plate (Al) and TE and TM light modes. The generated electromagnetic wave radiation is controlled by a soliton power, coupling coefficients, and ring radii within the system, where finally the near field radio wave is transmitted to the required therapeutic target (neural cells). Simulation results have shown that the temperature within the range from 40°C to about 46°C can be controlled and achieved.
Keywords: Plasmonic and Surface Plasmon Research